Building student preparedness and confidence: Insights from the global classroom mock job interview - Hanisah, Kasbon; Azimah, Ahmad Zaki; Farah Liyana, Ahmad A'azmey (UPM, 2024)
Should university students be equipped with formal lessons on career skills? We strongly believe the answer is yes, as it will prepare them with the necessary abilities and competencies for professional development and it would come in handy for their future job. Yet, a merely traditional formal learning method can be uninteresting, thus a more effective learning experience can be introduced including international collaborative approach. This innovative learning strategy which is known as Collaborative Online International Learning (COIL), has been a popular tool for promoting the internationalisation of a course syllabus (Rubin, 2017), as well as enhancing students’ learning experiences and intercultural understanding through a global partnership (Hackett et al., 2023).